Effects of Dormancy-Breaking Agents and Vernalization Temperatures on Dormancy Release and Sprouting of Shallot Bulbs - Masrinda Oktavia; Elkawakib Syam'un; Tigin Dariati (Universitas Panji Sakti, 2026)
Post-harvest dormancy in shallot (Allium cepa L. var. aggregatum) seed bulbs delays sprouting and disrupts planting schedules. While gibberellic acid (GA₃), hydrogen peroxide (H₂O₂), and vernalization each break dormancy, their combined effects have not been evaluated. The study, conducted in October 2025 at the Hasanuddin University Teaching Farm in Indonesia, is the first to evaluate the factorial effects of GA₃ or H₂O₂ combined with vernalization on dormancy breaking. Lokana shallot bulbs underwent vernalization for 14 days at room temperature, 5°C, or 10°C, followed by treatment with either no agent, GA₃ (100 mg L⁻¹, 6 h), or H₂O₂ (20%, 2 h), using a 3 × 3 randomized complete block design (27 plots, 1.215 plants). Data analysed using ANOVA followed by HSD at the 5% level and Pearson’s correlation. Significant interactions (p < 0.05) between dormancy-breaking agents and vernalization were observed for most germination rate and sprouting time parameters. The combination of H₂O₂ treatment with 5°C vernalization produced the fastest sprouting, achieving the highest sprouting rate index (SSI = 6.91) and rate coefficient (CVG = 12.78), the shortest mean sprouting time (MSpT = 7.86 days), and the lowest time to 50% sprouting (T50 = 7.06 days), outperforming both the control (SSI = 2.82; MSpT = 16.90 days; T50 = 16.86 days) and GA₃ treatments. Sprouting synchrony and uniformity remained unaffected. The combined application of H₂O₂ and short-duration cold vernalization represents a practical and cost-effective approach to reducing dormancy and expediting planting readiness in shallot seed production.